Grouping of Staphylococci on the Basis of Their Bacteriolytic-Activity Patterns: A New Approach to the Taxonomy of the Micrococcaceae - VARALDO, PIETRO E.; SATTA, GIUSEPPE (International Journal of Systematic and Evolutionary Microbiology, 1978)
A number of characters (colony features, biochemical and metabolic properties, susceptibility to antimicrobial agents) were determined on 1,054 staphylococci previously placed in six “lyogroups” on the basis of bacteriolytic activity. A great deal of uniformity was found among the characteristics of strains of the same lyogroup. Virtually 100% agreement was found between four of the six lyogroups and four nomen species or biotypes: i.e., lyogroup I was found to equate with Staphylococcus aureus; lyogroups II and III were found to equate with the recently described species S. simulans and S. capitis, respectively; and lyogroup V was found to equate with S. epidermidis sensu stricto. The occurrence of a relationship between the bacteriolytic activities of staphylococci and their cell wall compositions is shown. Such a correlation may be an expression of a specific mechanism of cell wall growth. The taxonomic significance of bacteriolytic activity and the relationship of this criterion and the resultant classificatory scheme to other criteria and schemes are discussed.